2018
DOI: 10.1002/ange.201809100
|View full text |Cite
|
Sign up to set email alerts
|

“On Water” Surface‐initiated Polymerization of Hydrophobic Monomers

Abstract: We present the "on water" surface-initiated Cumediated controlled radical polymerization ("on water" SI-CuCRP) that converts hydrophobic monomers in aqueous reaction medium to polymer brushes at unparalleled speed and efficiency.The method allows the facile conversion of avariety of common monomers under most simple reaction conditions and with minimal monomer amounts to thicka nd homogeneous polymer brushes.The highly living character of the "on water" SI-CuCRP allowed the preparation of decablock (homo)polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…13 An alternative, highly efficient approach to circumventing the need for deoxygenation relies on the use of zerovalent copper, Cu 0 , which acts as a source of active catalyst, 14,15 simultaneously consuming dissolved oxygen when the polymerization mixture is not directly exposed to air. 16,17 Although the robustness of Cu 0 -mediated SI-ATRP for the synthesis of multifunctional, gradient and microstructured polymer brushes has been already proven through the seminal works of Jordan et al [18][19][20] and also by several authors of the present work, 21,22 little has been revealed about the mechanism of this grafting process, and its tolerance to oxygen.…”
Section: Introductionmentioning
confidence: 72%
“…13 An alternative, highly efficient approach to circumventing the need for deoxygenation relies on the use of zerovalent copper, Cu 0 , which acts as a source of active catalyst, 14,15 simultaneously consuming dissolved oxygen when the polymerization mixture is not directly exposed to air. 16,17 Although the robustness of Cu 0 -mediated SI-ATRP for the synthesis of multifunctional, gradient and microstructured polymer brushes has been already proven through the seminal works of Jordan et al [18][19][20] and also by several authors of the present work, 21,22 little has been revealed about the mechanism of this grafting process, and its tolerance to oxygen.…”
Section: Introductionmentioning
confidence: 72%
“…13 Compared to the other SI-CRP methods, including those that make use of homogeneous catalytic systems, 20−23 as well as Cu(0) powder and wires, the simple and straightforward setup of SI-Cu(0) plate -CRP is advantageous. 11,15 A simple variation of the distance between the copper plate and the initiating substrate by tilting one or both the surfaces, or the use of a patterned Cu(0) plate, enable the preparation of defined brush gradients and structured polymer films. 11−13 Similarly easy is the fabrication of arrays of different polymer brushes on one substrate with the use of an intermediate mask.…”
mentioning
confidence: 99%
“…Finally, the precipitate was filtered using a Buchner funnel and washed several timed with distilled water and ethanol to remove monomers, oligomers and excess oxidant until the filtrate become almost colorless. At 80° C the precipitate was dried for 24h [63][64][65][66].…”
Section: Preparation and Characterization Of Panaa [Poly (Aniline-co-oanthranilic Acid)]mentioning
confidence: 99%
“…Al 2 O 3 nanoparticles were coated with different loadings of poly (aniline coanthranilic acid "PANAA") copolymer by using surface-initiated polymerization (SIP) method [63][64][65][66]. 8 ml conc.…”
Section: Preparation and Characterization Of Panaa/al2o3 Nanocompositementioning
confidence: 99%
See 1 more Smart Citation